Assessment of nanofiltration efficiency for simultaneous concentration of copper and recovery of acid from highly acidic wastewater - Bencheng Hu; Haowen Wu; Wenhao Su; Keyu Yao; Li Long; Pengfei Sun; Yongcheng Wang; Lin Lin; Hao Guo; Xiao-yan Li (Water Research, 2026)

Quantifying lamina-controlled variations in rock physical properties from AI-reconstructed 3D multimineral digital rocks - Yuqi Wu; Yumei Ao; Jiabao Yang; Zijie Lu; Keyu Liu; Yuchen Fan; Jianhua Zhao; Li Hou; Bo Liao; Pejman Tahmasebi (International Journal of Rock Mechanics and Mining Sciences, 2026)

UAV-based measurements of methane emissions from two electrically-driven natural gas compressor stations in China - Tianran Han; Wang Tian; Yuheng Zhang; Jietao Zhou; Yanrong Yang; Keyu Chen; Lei Ren; Chuanfeng Wang; Yufei Huang; Haijiong Sun; Xinyi Chen; Chang Liu; et al. (Environmental Pollution, 2026)

Towards complete utilization of rice husk components: A sequential process for the co-production of pectin, xylo-oligosaccharides, lignin-silica hybrid material, and fermentable sugars - Yuanxian Wu; Yuxin Xiao; Ronglian Hua; Keyu Chen; Yuanyuan Zhu; Junhua Zhang; Junjun Zhu (Biomass and Bioenergy, 2026)

Effect of arsenic-contaminated irrigation water exposeure combined with conventional and biodegradable microplastics on arsenic fractionation in the paddy soil - Haotian Yu; Fan Wu; Feng Peng; Keyu Long; Yihui Wei; Teng Ma (Environmental Pollution, 2026)

Stable versus transient sulfate–methane transition zone dynamics recorded by coexisting concretion types: Petrographic and in situ sulfur isotope evidence from Lower Silurian shale - Shichao Ji; Chao Liang; Jing Wu; Yingchang Cao; Keyu Liu; Fang Hao; Qing Tang (Chemical Geology, 2026)

Carbon isotope and mercury anomalies evidence across the Ordovician-Silurian boundary of volcanism accelerating the global carbon cycle - Haoran Xie; Chao Liang; Jing Wu; Yingchang Cao; Yu Han; Jiahong Wang; Keyu Liu; Fang Hao (Gondwana Research, 2026)

Diagenetic evolution of clay minerals and impacts on reservoir quality of the Wufeng and Longmaxi Shale in Sichuan Basin of China - Yang Chen; Jianhua Zhao; Qinhong Hu; Keyu Liu; Mengxiang Yu; Wei Wu; Chao Luo (Applied Clay Science, 2026)

Ankyrin-repeat transmembrane protein WAI-1 confers multiple disease resistance in wheat by activating autoimmunity - Qiuhong Wu; Wenling Li; Yongxing Chen; Huaizhi Zhang; Delin Li; Zhan Li; Fei Xiong; Guanghao Guo; Lei Dong; Xuejia Cui; Jingzhong Xie; Ping Lu; et al. (Science China Life Sciences, 2026)

Synergistic effects of pyrite and sludge biochar enhancing performance and reducing greenhouse gas emissions in constructed wetland-microbial fuel cells - Wang Maosen; Qin Yangyi; Wu Haiming; Zhao Jianguo; Zheng Lihe; Ding Keyu; Wang Baogui; Du Jingjing (Bioresource Technology, 2026)

Cerium-iron symbiotic nanozyme alleviates drought stress in wheat by targeting stomatal regulation and photosynthesis - Keyu Chen; Xiaowei Wang; Tao Yuan; Gehong Su; Chun Wu; Mengmeng Sun; Yanying Wang; Ming Hao; Xue Chen; Shiling Feng; Fuyong Wu; Dengcai Liu; et al. (Bioresource Technology, 2026)

Opportunities to enhance sugarcane yield and gross margin under climate change through irrigation and planting date adaptation - Shijin Yao; De Li Liu; Bin Wang; Siyi Li; Jonathan K. Webb; Keyu Xiang; Alfredo Huete; Lihong Wu; Hao Quan; Qiang Yu (Irrigation Science, 2026)

Alkali–organic synergy rewires microbial acid tolerance to restore nitrogen cycling in acidic soils - Mengke Li; Keyu Yao; Jean Damascene Harindintwali; Min Qian; Nan Wu; Yanwei Kan; Ziyi Song; Xian Xiao; Peng Liu; Yuan Zhao (Journal of Environmental Management, 2026)

Bacillus Cereus C3 Addition Facilitates Carbohydrate Degradation and Earthworm Growth During Vermicomposting of Sewage Sludge - Tiantian Tian; Xinge Cui; Wenxing He; Keyu Liu; Jiran Zhang; Shimin Zhang; Xitian Yang; Kun Wu; Xianqin Jiao; Shuxia Xu (Water, Air, & Soil Pollution, 2026)

‘1347B’ module confers durable stripe rust resistance in wheat - Hongkui Fu; Delin Li; Huaizhi Zhang; Yongxing Chen; Ping Lu; Miaomiao Li; Gaojie Wang; Keyu Zhu; Lei Dong; Jian Yang; Chunhuan Chen; Bin Bai; et al. (Theoretical and Applied Genetics, 2026)

Developmental stage-specific disruption of iron allocation by a ZmYSL2 mutation in maize - Yikai Wang; Kunfeng Zhang; Chuang An; Jiayi Liu; Hongmei Hu; Duo Shi; Jiaxin Shi; Keyu Zhao; Dan Liu; Ling Wu; Xiao Zhang; Bowen Luo; et al. (Planta, 2026)

Spatiotemporal variations of rainfall interception before and after implementation of Grain for Green Program in the Loess Plateau - Junyan Chen; Guozheng Liu; Jing Wu; Keyu Zhao; Tiegang Liu (Journal of Hydrology, 2026)

Mapping biology in space: from spatial transcriptomics platforms to analytical tools and databases - Zi-Zhen Guo; Renyan Wu; Weixiang Li; Keyu Yang; Xuexiang Ying; Hamid Alinejad-Rokny; Youqiong Ye (Science Bulletin, 2026)

The Role of Coagulation-Related Genes in Glioblastoma: A Comprehensive Analysis of the Tumor Microenvironment, Prognosis, and Treatment - Jingyi Yang; Lei Shen; Yuankun Cai; Ji Wu; Keyu Chen; Dongyuan Xu; Yu Lei; Songshan Chai; Nanxiang Xiong (Biochemical Genetics, 2026)

Rejection of geosmin and 2-methylisoborneol by polyamide membranes in drinking water treatment: Performance-energy efficiency evaluation and practical implications - Yuanyuan Sun; Keyu Yao; Haowen Wu; Yi Tao; Liping Jiang; Jianhua Qiu; Hao Guo (Water Research, 2026)

Lacustrine organic carbon burial in deep time: Perspectives from major geologic events and tectonic-climatic-ecological coupling - Chao Liang; Ao Chen; Yingchang Cao; Jing Wu; Yu Han; Keyu Liu; Guanghui Yuan; Fang Hao (Earth-Science Reviews, 2026)

ACSL4 Inhibition by AS-252424 Protects Visual Function by Suppressing RGC Ferroptosis After Retinal Ischemia Reperfusion Injury - Keyu Liu; Zihao Lin; Wu Xiang; Jiayi Zhang; Xiaofeng Wu; Chenzhao Ma; Yantao Wei; Jiawei Wang; Jianqiao Li (Molecular Neurobiology, 2026)

Responses of Phytoplankton Bloom Magnitude Off the Yangtze River Estuary to the Zonal Position of the Northwest Pacific Subtropical High - Qiong Wu; Keyu Hu; Bo Li; Tianqi Xiong; Hui Chen; Shaofeng Wang (International Journal of Climatology, 2025)
The phytoplankton bloom magnitude (PBM) off the Yangtze River Estuary has important responses to the changes in the east–west position of the northwest Pacific subtropical high (NWPSH). The potential physical mechanism is analyzed through observations and a physical–biogeochemical model. Results reveal that the anomalously high precipitation in June–July increases the extension ranges of low salinity and high NO 3 concentration water in NWPSH westward extension years. However, due to persistent cloudy and rainy weather, the light condition is unfavorable for the explosive growth of phytoplankton. When the NWPSH moves northward in August, the study area is controlled by anomalously anticyclonic circulation; hot and sunny weather prevails, the nutrients carried by the Yangtze River discharge during the previous June–July period continue to extend toward Jeju Island with the diluted water, favoring the explosive growth of phytoplankton, and vice versa. Sensitivity experiments reveal that when the June–July averaged river discharge and nutrients in NWPSH westward extension years are twice those in normal years, the range of phytoplankton blooms in August can extend to 124.2° E. When the June–July averaged river discharge and nutrients in NWPSH westward extension years are only 0.5 times those in normal years, the range of phytoplankton blooms in August only extends to 123° E. Therefore, the changes in river discharge and nutrient expansion range caused by the east–west position changes of the NWPSH in June–July are important reference indicators for phytoplankton bloom variations throughout the summer. The study provides new scientific reference for seasonal phytoplankton bloom forecasting off the Yangtze River Estuary.

Spatial accessibility to public electric vehicle charging infrastructure and multi-mechanism process of regional inequity in Greater Bay Area, China - Xing Gao; Huizi Wang; Ying Zhang; Keyu Zhai; Meiling Wu (Journal of Transport Geography, 2025)

Paleoenvironment and organic matter enrichment in the Kaijiang–Liangping Trough across the Emeishan Large Igneous Province (ELIP) - Mengxiang Yu; Jianhua Zhao; Keyu Liu; Qinhong Hu; Wei Wu; Quanyou Liu; Chao Luo; Yang Chen; Hongyu Ma; Zhijun Jin (Marine and Petroleum Geology, 2025)

Phenotypic and transcriptomic insights into the antibacterial effects of magnolol against the novel pathogen Vibrio misgurnus - Keyu Zhou; Qibin Jiang; Bowen Huang; Kun Peng; Mingqi Ai; Le Xu; Songmao Wu; Ping Ouyang; Xiaoli Huang; Defang Chen; Yi Geng (Aquaculture International, 2025)

Morphology and in-situ sulfur isotope characteristics of pyrite across the Ordovician-Silurian boundary marine shale in South China: Indicative significance for sedimentary environment - Shichao Ji; Chao Liang; Yu Han; Qing Tang; Yingchang Cao; Keyu Liu; Jing Wu; Haoran Xie; Fanglu Chen (Marine and Petroleum Geology, 2025)

Characterizing multi-scale heterogeneities in shales: An innovative workflow and application to Paleogene lacustrine shales in the Subei Basin, eastern China - Zongguang Guo; Keyu Liu; Lingjie Yu; Jie Chen; Yuqi Wu; Lei Chen; Chao Liang (Marine and Petroleum Geology, 2025)

Sensitive lateral flow immunoassay enabled by signal amplification strategy with high active oxidase-like nanozymes - Jie Zhu; Yunhui Cheng; Xufeng Wang; Hao Wu; Ye Jiao; Keyu Xing; Li Yao; Pei Jia; Zhou Xu (Food Bioscience, 2025)

How does greenness contribute to reducing lung cancer risks associated with particulate matter exposure? - Keyu Luo; Huagui Guo; Weifeng Li; Jiansheng Wu (Atmospheric Pollution Research, 2025)

Investigation on the packing and hydration homogeneity of bentonite pellet mixtures - Shixiang Hu; Yunzhi Tan; De’an Sun; Keyu Wu (Annals of Nuclear Energy, 2025)

Response of sea-surface partial pressure of CO2 to ENSO events over the Taiwan Strait - Keyu Hu; Qiong Wu; Tianqi Xiong; Bo Li; Peng Bai; Zhenxin Ruan; Chengcheng Yu (Acta Oceanologica Sinica, 2025)

Spatiotemporal changes and management measure to enhance ecosystem services in the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Yadong Liu; Xuchun Yan; Xiaoying Fan; Avirmed Dashtseren; et al. (Environmental Development, 2024)

Spatial mapping of greenhouse gases using a UAV monitoring platform over a megacity in China - Tianran Han; Conghui Xie; Yanrong Yang; Yuheng Zhang; Yufei Huang; Yayong Liu; Keyu Chen; Haijiong Sun; Jietao Zhou; Chang Liu; Junfei Guo; Zhijun Wu; et al. (Science of The Total Environment, 2024)

Development of a CRISPR/Cas12a-based method to detect invasive aquatic species - Minlin Zhang; Xiaoling Zuo; Jiantao Liang; Keyu Lu; Liyun Wei; Xu Yan; Huihong Zhao; Songyong Gan; Jinhui Wu; Qing Wang (Aquaculture, 2024)

Unleashing hidden carbon sequestration potential: A case study of the Greater Bay Area, China - Keyu Luo; Zhenyu Wang; Weifeng Li; Jiansheng Wu (Urban Climate, 2024)

Corrigendum to “An end-to-end approach to predict physical properties of heterogeneous porous media: Coupling deep learning and physics-based features” [Fuel 352 (2023) 128753] - Yuqi Wu; Senyou An; Pejman Tahmasebi; Keyu Liu; Chengyan Lin; Serveh Kamrava; Chang Liu; Chenyang Yu; Tao Zhang; Shuyu Sun; Samuel Krevor; Vahid Niasar (Fuel, 2024)

A stronger association of mental disorders with smaller particulate matter and a modifying effect of air temperature - Keyu Wu; Junwen Tao; Qiyue Wu; Hong Su; Cunrui Huang; Qingrong Xia; Cuizhen Zhu; Jing Wei; Min Yang; Junwei Yan; Jian Cheng (Environmental Pollution, 2024)

Salinization mechanism of lakes and controls on organic matter enrichment: From present to deep-time records - Chao Liang; Bo Yang; Yingchang Cao; Keyu Liu; Jing Wu; Fang Hao; Yu Han; Wanlu Han (Earth-Science Reviews, 2024)

Moderate grazing increased carbon, nitrogen and phosphorus storage in plants and soil in the Eurasian meadow steppe ecosystem - Miao Wang; Chu Zhang; Sisi Chen; Yu Zhang; Tianqi Yu; Xiaojuan Xue; Lianhai Wu; Wenneng Zhou; Xiangjun Yun; Ruirui Yan; Keyu Bai (Science of The Total Environment, 2024)

Interfacial characteristics and mechanical behavior of geopolymer stabilizers with clay mineral: A molecular dynamics study - Dazhi Wu; Kaiquan Cao; Keyu Chen; Ningning Mao (Applied Clay Science, 2024)

Characteristics, origins, and significance of pyrites in deep-water shales - Chao Liang; Shichao Ji; Yingchang Cao; Keyu Liu; Jing Wu; Fang Hao (Science China Earth Sciences, 2024)

How does grazing pressure affect feed intake and behavior of livestock in a meadow steppe in northern China and their coupling relationship - Tianqi Yu; Ruirui Yan; Chu Zhang; Sisi Chen; Zhitao Zhang; LeiFeng Guo; Tianci Hu; Chengxiang Jiang; Miao Wang; Keyu Bai; Wenneng Zhou; Lianhai Wu (Science of The Total Environment, 2024)

The influence of asphaltene matrix on the thermal evolution of polycyclic aromatic hydrocarbons: Experimental evidence and geochemical implications - Peng Fang; Zhibin Hong; Jia Wu; Yuan Wang; Keyu Liu; Minghui Zhou (Journal of Asian Earth Sciences, 2024)

Eliminating concentration polarization with gradient lithiophilic sites towards high performance lithium metal anodes under low N/P ratio - Zichun Xiao; Duzhao Han; Yu Fu; Keyu Xie; Wensheng Tian; Chengyong Shu; Kai Xi; Chengxin Peng; Yuping Wu; Shixue Dou; Wei Tang (Chemical Engineering Journal, 2024)

Stochastic and deterministic assembly processes of bacterial communities in different soil aggregates - Yan Wang; Kun Zhu; Xin Chen; Keyu Wei; Rong Wu; Gang Wang (Applied Soil Ecology, 2024)

Seasonal peak and the role of local weather in schizophrenia occurrence: A global analysis of epidemiological evidence - Jihong Hu; Yufan Feng; Hong Su; Zhiwei Xu; Hung Chak Ho; Hao Zheng; Wenyi Zhang; Junwen Tao; Keyu Wu; Mohammad Zahid Hossain; Yunquan Zhang; Kejia Hu; et al. (Science of The Total Environment, 2023)

An end-to-end approach to predict physical properties of heterogeneous porous media: Coupling deep learning and physics-based features - Yuqi Wu; Senyou An; Pejman Tahmasebi; Keyu Liu; Chengyan Lin; Serveh Kamrava; Chang Liu; Chenyang Yu; Tao Zhang; Shuyu Sun; Samuel Krevor; Vahid Niasar (Fuel, 2023)

Mixing processes and patterns of fluids in alkane-CO2-water systems under high temperature and high pressure—Microscopic visual physical thermal simulations and molecular dynamics simulations - Guanghui Yuan; Shuqi Wu; Yingchang Cao; Zihao Jin; Keyu Liu; Yanzhong Wang (Science China Earth Sciences, 2023)

Differential hydrocarbon generation and evolution of typical terrestrial gas-prone source rocks: An example from the Kuqa foreland basin, NW China - Jianliang Liu; Xianzhang Yang; Keyu Liu; Zhenping Xu; Kun Jia; Lu Zhou; Hongxing Wei; Liang Zhang; Shaojun Wu; Xinzhuo Wei (Marine and Petroleum Geology, 2023)

Cross-sectional Exploration of the Relationship Between Glutamate Abnormalities and Tic Disorder Severity Using Proton Magnetic Resonance Spectroscopy - Juanjuan Hao; Xin Zhang; Ying Liu; Zhongyang Zhang; Keyu Jiang; Xiao-Yong Zhang; Min Wu (Phenomics, 2023)

Spatiotemporal variations and driving factors for potential wind erosion on the Mongolian Plateau - Xianhua Wei; Xiaodong Wu; Dong Wang; Tonghua Wu; Ren Li; Guojie Hu; Defu Zou; Keyu Bai; Xin Ma; Yadong Liu; Xuchun Yan; Xiaoying Fan; et al. (Science of The Total Environment, 2023)

A systematic review and meta-analysis of air pollution and angina pectoris attacks: identification of hazardous pollutant, short-term effect, and vulnerable population - Min Yang; Keyu Wu; Qiyue Wu; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Junwen Tao; Hao Zheng; Mohammad Zahid Hossain; Wenyi Zhang; Ning Wang; Hong Su; et al. (Environmental Science and Pollution Research, 2023)

Abnormal ambient temperature change increases the risk of out-of-hospital cardiac arrest: A systematic review and meta-analysis of exposure types, risk, and vulnerable populations - Qiyue Wu; Min Yang; Keyu Wu; Hong Su; Cunrui Huang; Zhiwei Xu; Hung Chak Ho; Hao Zheng; Wenyi Zhang; Junwen Tao; Thi Anh Thu Dang; Mohammad Zahid Hossain; et al. (Science of The Total Environment, 2023)

Associations between exposure to brominated flame retardants and metabolic syndrome and its components in U.S. adults - Zhiqiang Che; Huixun Jia; Renjie Chen; Keyu Pan; Zhe Fan; Chang Su; Zhenyu Wu; Tao Zhang (Science of The Total Environment, 2023)

Degradation of lomefloxacin by MoS2/MIL-53(Fe, Cu) catalyst in heterogeneous electro-Fenton process - Lei Fang; Guojian Wu; Keyu Yao; Dongyang Zhang; Yongchao Zhou (Environmental Science and Pollution Research, 2023)

Therapeutic implications of functional tea ingredients for ameliorating inflammatory bowel disease: a focused review - Yina Huang; Keyu Xing; Liang Qiu; Qinglong Wu; Hua Wei (Critical Reviews in Food Science and Nutrition, 2022)

Fine mapping of powdery mildew resistance gene MlWE74 derived from wild emmer wheat (Triticum turgidum ssp. dicoccoides) in an NBS-LRR gene cluster - Keyu Zhu; Miaomiao Li; Haibin Wu; Deyun Zhang; Lingli Dong; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Guanghao Guo; Huaizhi Zhang; Panpan Zhang; et al. (Theoretical and Applied Genetics, 2022)

Resistance of blended alkali-activated fly ash-OPC mortar to mild-concentration sulfuric and acetic acid attack - Keyu Chen; Dazhi Wu; Sijia Fei; Chonggen Pan; Xinyuan Shen; Chaoxia Zhang; Juntao Hu (Environmental Science and Pollution Research, 2022)

Interactions between hydrocarbon-bearing fluids and calcite in fused silica capillary capsules and geological implications for deeply-buried hydrocarbon reservoirs - Zihao Jin; Guanghui Yuan; Yingchang Cao; Keyu Liu; Yanzhong Wang; Jianye Sun; Xiluo Hao; Ling Zhou; Yihan Wei; Shuqi Wu (Science China Earth Sciences, 2022)

Identification and fine mapping of spot blotch (Bipolaris sorokiniana) resistance gene Sb4 in wheat - Panpan Zhang; Guanghao Guo; Qiuhong Wu; Yongxing Chen; Jingzhong Xie; Ping Lu; Beibei Li; Lingli Dong; Miaomiao Li; Rongge Wang; Chengguo Yuan; Huaizhi Zhang; et al. (Theoretical and Applied Genetics, 2020)

Development of a compact continuum tubular robotic system for nasopharyngeal biopsy - Liao Wu; Shuang Song; Keyu Wu; Chwee Ming Lim; Hongliang Ren (Medical & Biological Engineering & Computing, 2017)